1984
DOI: 10.1177/002383098402700405
|View full text |Cite
|
Sign up to set email alerts
|

Linking as a Marker of Fluent Speech

Abstract: A two-dimensional, speech dynamic analysis of natural speech identifies linking (liaison) as a prominent class of phenomena at the phonetic syllabic level. Consonant Attraction, the specific feature under experimental observation, is highly prevalent in casual English speech both in terms of absolute frequency and in a ratio of potential to actualized link points. A statistically significant difference between native and nonnative speech can be noted for this fluency phenomenon. It points to the role this and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
43
0
3

Year Published

1989
1989
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(48 citation statements)
references
References 4 publications
2
43
0
3
Order By: Relevance
“…Hieke (1984) found that while native English speakers realized 77.3 percent of all potential link points for consonant attraction in spoken discourse, native German speakers at a fairly advanced level of proficiency realized only 53.5 percent of those links in English discourse. In a similar vein, Odlin (1978) demonstrated a correlation between overall proficiency level and use of contractions in the speech of ESL learners.…”
Section: Teaching Approachesmentioning
confidence: 92%
See 1 more Smart Citation
“…Hieke (1984) found that while native English speakers realized 77.3 percent of all potential link points for consonant attraction in spoken discourse, native German speakers at a fairly advanced level of proficiency realized only 53.5 percent of those links in English discourse. In a similar vein, Odlin (1978) demonstrated a correlation between overall proficiency level and use of contractions in the speech of ESL learners.…”
Section: Teaching Approachesmentioning
confidence: 92%
“…The pronunciation of individual phonemes is greatly influenced by such factors as speaking style (Beebe 1980, Schmidt 1977, rhythm (Adams 1979, Gilbert 1984) and speaking rate (Fowler 1981, Hieke 1984. Moreover, the development of individual phonemes in second language acquisition is closely tied to the development of a variety of properties affecting stretches of speech (Pennington 1987), referred to as suprasegmental properties or features.…”
Section: Components Of Pronunciationmentioning
confidence: 99%
“…It is striking, for example, that although it clearly typifies American English, until very recently little note has been taken of the fact that all casual speech (and much deliberate speech, for that matter) is marked by frequent syllabic restructuring. This in turn can radically change the familiär citation forms of words (and is so pervasive äs to affect on the average every sixth syllablel; Hieke 1984). The unfortunate misnomer of 'fast speech' rules (rather than 'normal speech' rules) in the literature makes resyllabication appear even more unusual and exceptional, with the result that scant attention has ever been paid to the entire problem complex in ESL/EFL teaching materials.…”
Section: The Resolution Of Language From Speechmentioning
confidence: 99%
“…bursts of speech bordered by pauses and under the umbrella of a single Intonation contour). To capture the various processes of assimilation, reduction, loss of features, even syllables, all of which can be expressed and explained under absorption (Hieke 1984), a separate speech dynamic dorn a in has been posited. The fundamental dichotomy between the citation form domain and the speech dynamic domain is readily demonstrated.…”
Section: The Resolution Of Language From Speechmentioning
confidence: 99%
See 1 more Smart Citation